Studying the effect of light intensity and the dust on efficiency of Silicon Solar cell - Kawkab D. Salim (Tikrit Journal of Pure Science, 2021)
In this paper, Two main effected parameters on the efficiency of solar cell has studied: the increasing in the amount of intensity of incident solar irradiance on the surface of silicon solar cell and accumulation of dust on the front face of solar cell. The parameters of silicon solar cell (Isc, Voc, pmax, η) have been studied under various quantities of solar irradiations (G= 100, 172,252 and 606W/m2 ) at  a constant temperature (TC=25±2) ͦ C. The results showed an increasing in the value of conversion efficiency( fromη=7.1% to η=10%) with the increasing of intensity of solar flux. But the dust had a reverse effect on the value of conversion efficiency , thus after one week  there was noticeable of(∆Isc= 5%) degradation at value of short circuit that lead to decrease of conversion efficiency.